Análise do modelo de gestão implantado no Centro de Atenção Psicossocial CAPS II OESTE de 1995 a 2005, situado no distrito sanitário Oeste do município de Natal/RN, à luz da Co-gestão - Dias, Jaidê de Barros (2007)
This dissertation has as aim the praxis of co-management of the health service of CAPS II OESTE of Natal-RN, where health workers, family members got to materialize guidelines and principles of psychiatric Brazilian reform in real possibilities of subjectivity construction, whereas they changed social relations in daily life. The path chosen to record was from testimonials and contributions of those who meant their done. Redeeming this story from social representations of the majority of their builders was an instigating, delicate and rewarding task, emphasizing the living memory, rebuilt in a line of time which could not be found in simple documentary collections. Mainly, by knowing that service routine was intense and had as characteristic the singular mobility itself from a creation process and therefore not always its dynamic allowed adequate records. At the same time, from this occurred the field and bibliographic research which allowed the detailed information from the prior milestones and motivated to the practice here reported. The rereading of concepts in an interface with the reports of the interviewees enabled the verification that the model of mental health advocated by psychiatric reform was understood. Once noticed the presence of the beliefs and values of people in motivating energy for the progress of reform, it has gone to fetch theoretical subsidies of administrative order to understand how they saw this building and that uniqueness has been printed. The theoretical way and praxis have tracked here has allowed to analyze how occurred such a process of production and subjectivity and collectives that when organize enabled themselves for analysis and intervention, including in crisis situations. Therefore, it was revealed that ethical and multi-disciplinarity, the humanitarian sense, the coresponsibility, co-production and horizontal management were the key factors for spread from a changing protagonist. One can thus conclude that co-management from that collective has been multi-disciplinary weaving a cross